The role of transportation disadvantage for women on community supervision - Bohmert, Miriam Northcutt (Criminal justice and behavior, 2016)
Access to transportation (i.e., walking, public transit, personal vehicles), or lack thereof, has not been extensively explored in criminal justice samples. Consequently, mixed-methods study of 366 women on probation and parole is the first to define transportation disadvantage, document its prevalence, and explore the problems related to it. Findings point to four themes, discovered in quantitative data analysis and buttressed by qualitative accounts, that illuminate the importance of transportation to justice-involved women. First, women have extensive transportation deficits at the individual level (e.g., they have poor physical health). Second, women rely heavily on social support. Third, women have deficits at the community level (e.g., they reside in inaccessible areas). Fourth, women have trouble identifying transportation-related problems directly, but through their narratives identify 10 distinct types. Further, transportation was a pressing concern for 42.6% of women that coincides with other needs such as health, safety, employment, neighborhood accessibility, and social support.